Organic structure determination using 2-D NMR spectroscopy : a problem-based approach - Simpson, Jeffrey H. (Burlington, Boston : Academic Press, 2012)
'The second edition of this book comes with a number of new figures, passages, and problems. Increasing the number of figures from 290 to 448 has necessarily added considerable length, weight, and, expense. It is my hope that the book has not lost any of its readability and accessibility. I firmly believe that most of the concepts needed to learn organic structure determination using nuclear magnetic resonance spectroscopy do not require an extensive mathematical background. It is my hope that the manner in which the material contained in this book is presented both reflects and validates this belief'--
Includes bibliographical references and index.
Keywords: Molecular structure; Organic compounds -- Analysis; Nuclear magnetic resonance spectroscopy